Abiotic Factors Affecting Canola Establishment and Insect Pest Dynamics. (4th January 2012) - Nansen Nansen, Christian Christian; Trostle Trostle, Calvin Calvin; Angadi Angadi, Sangu Sangu; Porter Porter, Patrick Patrick; Martini Martini, Xavier Xavier
Abstract : Canola is grown mainly as an oil-seed crop, but recently the interest in canola has increased due to its potential as a biodiesel crop. The main objectives of this paper were to evaluate effects of abiotic factors and seed treatment on canola plant establishment and pest pressure in the Southern High Plains of Texas. Data was collected at two field locations during the first seven months of two field seasons. Based on multi-regression analysis, we demonstrated that precipitation was positively associated with ranked plant weight, daily minimum relative humidity and maximum temperature were negatively associated with plant weight, and that there may be specific optimal growth conditions regarding cumulative solar radiation and wind speed. The outlined multi-regression approach may be considered appropriate for ecological studies of canola establishment and pest communities elsewhere and therefore enable identification of suitable regions for successful canola production. We also demonstrated that aphids were about 35% more abundant on non-treated seeds than on treated seeds, but the sensitivity to seed treatment was only within four months after plant emergence. On the other hand, seed treatment had negligible effect on presence of thrips.